Pengaruh Pemahaman Akuntansi, Sastra Keuangan dan Lingkungan Kampus Untuk Mahasiswa Manajemen Keuangan - Sugiarto Abdullah; Dwiyani Sudaryanti; Arista Fauzi Kartika Sari (e_Jurnal Ilmiah Riset Akuntansi, 2023)
The purpose of this study is to determine the impact of students' understanding of accounting, financial literacy, and the campus environment on financial management. The independent variables in this study were accounting literacy, financial literacy, and campus environment, and the dependent variable was student financial management. This type of research is quantitative as the data used are numerical. The data source for this study is primary data from survey methods such as questionnaires. The population of this survey in 2019 consisted of accounting majors from the Faculty of Economics, Malang Islamic University. The records series method used the Slovin formula. Based in this method, 68 students majoring in accounting used the class in 2019. Hypothesis testing used descriptive statistical analysis, instrumental testing, normality testing, classical hypothesis testing, multiple linear analysis testing, and SPSS version 24 hypothesis testing. The results show that understanding of variable accounting does not affect students' financial management (0.587 > 0.05), variable financial literacy has a large positive impact on students' financial management (0.000 < 0.05), Variable campus environment affects student financial management (0.029 < 0.05).Keywords: Understanding of accounting, financial literacy, campus environment, and student financial management.